Social Pedagogy in the Context of Values – as Seen by Selected Authors – Fields of Inquiry: The Perspective of Polish Social Pedagogy - Mariusz Cichosz (Paedagogia Christiana)
The subject of values is a key, even fundamental issue for the social sciences, especially the practically oriented ones – consequently, also for social pedagogy. They (values) can be identified best by analysing the subject-matter of social pedagogy, which is always dissected in the basic source scheme of this field, i.e., the one that deals with the relationship between the human/individual and the environment. It is in connection with this relationship that the theories and concepts of this pedagogy are developed and practical solutions are adopted for organising the human living environment. The analysis of the accepted interpretations of this relationship by different authors and Polish social educators that has been presented in this paper shows existing regularities in this regard.